Social and economic changes in the province of Scythia (4th–6th centuries) - Barnea, Alexandru (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes social and economic transformations in the province of Scythia in the 4th–6th centuries. The research problem concerns changes in social structure and their impact on the regional economy. The aim of the work is to reconstruct these processes in the context of the Late Roman Empire. The author applies analysis of historical and epigraphic sources. The most important results indicate the growing importance of craftsmen and merchants and the simultaneous decline of the traditional urban aristocracy and curiales. Soldiers, officials, and clergy also played an important role. There was a gradual decline of slavery and the transformation of slaves into coloni. A characteristic feature of the region was the importance of limitanei, who performed both military and agricultural functions. The conclusion is that these transformations reflect the transition from an ancient economy to early medieval structures.